A (re)construção da prática pedagógica de professores de língua inglesa - Marques, Sandra Mari Kaneko [UNESP] (My University, 2010)
This papaer's main objective is to discuss partial data collected for an ongoing reserch wich aims at investigating the pedagogical pratice (re) construction process in Teaching Pratice as part of a pre-service teacher education course.
Keywords: Prática de ensino; Reflexão; Formação de professores